Perkembangan Kognitif Anak Usia 5 Tahun Mengenal Jenis Jenis Tanaman Menggunakan Instrumen Asesmen Checklist - Claudia Cresensia Sembiring; Dinda Aulina Sinaga; Erika Sihite; Najwa Rana Ismawan; Tsalitsa Gunawan Silalahi; Wilde Dosta Cristina Silalahi; Imel Betsaida Lingga (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Cognitive development in early childhood, especially 5 years of age, is an important foundation in forming logical and symbolic thinking skills. Although some children are able to recognize and name various types of plants in their environment, there is still variation in understanding the physical characteristics of plants and their habitats. This study aims to describe the cognitive abilities of 5-year-old children in identifying plant types, recognizing where they grow, and understanding the physical characteristics of plants through a checklist-based assessment approach. The study used a descriptive quantitative method with seven children from five kindergartens in Medan City as subjects. Data were collected through direct observation, interviews, and documentation of children's activities during the learning process. The results of the study showed that most children, namely 85.71%, were in the "Very Well Developed" category. Children were able to group plants based on their type and where they grow, and recognize plant parts such as roots, stems, leaves, and flowers. These findings indicate that the use of checklist-based observation assessment instruments is effective in mapping children's cognitive development more objectively and contextually. This study contributes to the development of early childhood education learning strategies that are more appropriate to children's developmental stages and based on real experiences.